Spinnable mesophase pitch as well as preparation method and application thereof

By mixing asphalt with a polycyclic compound containing a hexa-membered cycloalkane structure for polymerization, spinable mesophase asphalt is prepared, which solves the problems of unstable spinning continuity and structural defects of mesophase asphalt in the prior art, and achieves the production of carbon fibers with high content and excellent mechanical properties.

CN119685045APending Publication Date: 2025-03-25CHINA UNIV OF MINING & TECH (BEIJING)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411881599.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

In the prior art, the mesophase bitumen of asphalt-based carbon fibers has continuity and structural defects during the spinning process, resulting in insufficient performance, and the residues of catalysts and hydrogen-supply reagents affect the performance of the final product.

Method used

By mixing the asphalt with a polycyclic compound containing a hexa-membered cycloalkane structure and polymerizing under the protection of an inert protective gas, a spunable mesophase asphalt is obtained. This method does not require the addition of catalysts, and makes full use of hydrogen supply reagents to simplify the process flow.

Benefits of technology

The high content of mesophase asphalt and excellent melt spinning continuity are achieved. The diameter of the monofilament is less than 15 microns, the continuous spinning time can reach 90 minutes, and the length of the monofilament can exceed 20,000 meters. At the same time, the mesophase bituminous carbon fiber has excellent mechanical properties, with a tensile strength up to 1400MPa and a tensile modulus up to 200GPa.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119685045A_ABST
    Figure CN119685045A_ABST
Patent Text Reader

Abstract

The invention provides spinnable mesophase pitch as well as a preparation method and application thereof, and belongs to the technical field of synthetic pitch preparation. The preparation method of the spinnable mesophase pitch provided by the invention comprises the following steps: mixing pitch with a polycyclic compound containing a six-membered naphthenic structure, and carrying out polymerization reaction under the protection of inert protective gas to obtain the spinnable mesophase pitch, the polymerization reaction comprises a closed heating stage, a constant-temperature self-boosting stage and a constant-temperature purging stage. The polycyclic compound containing the six-membered naphthenic structure can provide a naphthenic structure and a hydrogenation environment, so that the raw material asphalt does not need to be subjected to independent hydrotreating, the excessive polymerization of the mesophase asphalt is inhibited, and the stacking of molecules and the growth of the mesophase are facilitated. According to the preparation method, a catalyst does not need to be added, a hydrogen donor reagent does not need to be removed, no new impurity is generated in the preparation process, the process is simple, and the preparation cost of the mesophase pitch can be effectively reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of synthetic asphalt preparation, and in particular to a spinnable mesophase asphalt and a preparation method and application thereof. Background Art

[0002] As an excellent structural reinforcement material, carbon fiber has mechanical and transportation properties, and is widely used in military, aircraft and aerospace fields. Carbon fiber is divided into polyacrylonitrile-based (PAN), asphalt-based and viscose-based fibers according to the different precursors. PAN-based and asphalt-based carbon fibers are the most widely used high-performance carbon fibers.

[0003] Compared with PAN-based carbon fibers, which are currently the largest in production, asphalt-based carbon fibers have a wide range of raw material sources and price advantages. In addition to showing similar mechanical properties to PAN-based carbon fibers, asphalt-based carbon fibers are more likely to achieve higher modulus and thermal and electrical conductivity. Therefore, asphalt-based carbon fibers prepared with asphalt as raw material have broader application prospects. Asphalt-based carbon fibers can be obtained by spinning mesophase asphalt. However, asphalt, as a precursor for synthesizing mesophase asphalt, is a dark brown complex mixture composed of hydrocarbons and their non-metallic derivatives of different molecular weights. The main components are polycyclic and condensed aromatic hydrocarbons and their derivatives. The specific compound composition is very complex. Asphalt can be divided into coal tar pitch, petroleum asphalt, biomass asphalt and synthetic asphalt according to raw materials. Among them, coal tar pitch has a higher softening point and viscosity due to its high aromaticity and lack of cycloalkane structure and short-chain aromatic hydrocarbons, which is not conducive to the continuity and stability of spinning, and also limits the application of coal tar pitch-based carbon fibers to a certain extent. Other asphalts directly used as precursors for the synthesis of spinnable mesophases also have inherent structural defects that affect their spinning continuity. Therefore, the asphalt needs to be modified to varying degrees, such as component separation, catalytic polymerization or co-carbonization modification, all of which aim to introduce a certain degree of cycloalkane structure and short-chain aromatics to improve the spinning stability of the mesophase asphalt. However, during the asphalt modification process, the residues of catalysts and hydrogen donors will affect the final performance of the product, and the removal of the catalyst is cumbersome and difficult to ensure complete removal of the catalyst. The removal of the hydrogen donor also requires a lot of energy consumption. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a spinnable mesophase pitch and a preparation method thereof. The preparation method does not add a catalyst and fully utilizes an added hydrogen supply reagent, so that it can be suitable for the application of preparing mesophase pitch.

[0005] The present invention provides a method for preparing a spinnable mesophase pitch, comprising the following steps:

[0006] The asphalt is mixed with a polycyclic compound containing a six-membered cycloalkane structure, and a polymerization reaction is carried out under the protection of an inert protective gas to obtain a spinnable mesophase asphalt; the polymerization reaction includes a closed heating stage, a constant temperature self-pressure stage and a constant temperature purge stage.

[0007] Optionally, the ash content of the asphalt is ≤0.01% by mass, and the quinoline insoluble matter content is ≤0.01% by mass, and the asphalt includes one or more of coal asphalt, petroleum asphalt and biomass asphalt.

[0008] Optionally, the polycyclic compound containing a six-membered cycloalkane structure is at least one of tetralin and decalin.

[0009] Optionally, the mass ratio of the asphalt to the polycyclic compound containing a six-membered cycloalkane structure is 5-20:1.

[0010] Optionally, the polymerization reaction is carried out under stirring conditions, and the stirring rate is 100-1000r / min.

[0011] Optionally, the closed heating stage is to heat the mixture to a polymerization reaction temperature at a heating rate of 1-5°C / min, wherein the polymerization reaction temperature is 350-450°C.

[0012] Optionally, the constant temperature self-pressurization stage is a constant temperature reaction for 1-12 hours at the polymerization reaction temperature.

[0013] Optionally, the constant temperature purging stage is to introduce an inert protective gas into the bottom of the reaction solution at the polymerization reaction temperature for constant temperature purging for 1-12 hours, wherein the flow rate of the constant temperature purging is 7-35 mL / (g·min).

[0014] The present invention also provides a spinnable mesophase pitch prepared by the preparation method described in any one of the above technical solutions.

[0015] The present invention also provides a use of the spinnable mesophase pitch described in the above technical solution in preparing carbon fibers.

[0016] Compared with the prior art, the present invention has the following beneficial effects:

[0017] The polycyclic compound containing a six-membered cycloalkane structure used in the present invention can provide a cycloalkane structure and a hydrogenation environment, improve the H / C ratio of the raw material, and make the raw asphalt do not need to be hydrogenated separately; and after the compound containing the six-membered cycloalkane structure is hydrogenated, it will condense to form a compound with an aromatic ring structure, and participate in the stacking of carbon layers and the growth of the mesophase. When it is partially cracked, a certain amount of alicyclic structure and alkyl side chain will be introduced into the system, thereby providing more hydrogen transfer, inhibiting the excessive polymerization of the mesophase asphalt, and facilitating the stacking of molecules and the growth of the mesophase. The preparation method does not add a catalyst, and does not need to remove the hydrogen supply reagent, which saves the energy consumption required for removing the hydrogen supply reagent. No new impurities are generated during the preparation process, and the process is simple, which can effectively reduce the preparation cost of the mesophase asphalt.

[0018] It can be seen from the embodiments of the present invention that the mesophase pitch prepared by the present invention does not need to add a catalyst, nor does it need to remove a hydrogen supply agent, has a high mesophase content, has excellent melt spinning continuity, and has a single filament diameter of less than 15 microns, a single filament continuous spinning time of up to 90 minutes, and a single filament length of up to 20,000 meters. In addition, the mesophase pitch-based carbon fiber obtained by the preparation method of the present invention has excellent mechanical properties, and its tensile strength can reach 1400MPa and its tensile modulus can reach 200GPa. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The above and other objects, features and advantages of the present invention will be apparent from the following description of preferred embodiments and accompanying drawings which illustrate the subject matter of the present invention and its use, in which:

[0020] Figure 1 A schematic diagram of the preparation process of spinnable mesophase pitch provided in an embodiment of the present invention.

[0021] Figure 2 Polarized light microscope image of the spinnable mesophase pitch provided in an embodiment of the present invention.

[0022] Figure 3 This is a time-of-flight mass spectrum of the spinnable mesophase pitch provided in an embodiment of the present invention.

[0023] Figure 4 This is a scanning electron microscope image of the carbon fiber structure prepared from the spinnable mesophase pitch provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0024] The present invention will be described below by specific embodiments, and it will be appreciated by those skilled in the art that the specific embodiments below are only for illustrative purposes, and do not limit the scope of the present invention in any way. In addition, in the following embodiments, unless otherwise specified, the materials and equipment used are all commercially available. If in the following embodiments, specific treatment conditions and treatment methods are not clearly described, then conditions and methods known in the art can be used to process.

[0025] The present invention provides a method for preparing a spinnable mesophase pitch, comprising the following steps:

[0026] The asphalt is mixed with a polycyclic compound containing a six-membered cycloalkane structure, and a polymerization reaction is carried out under the protection of an inert protective gas to obtain a spinnable mesophase asphalt; the polymerization reaction includes a closed heating stage, a constant temperature self-pressure stage and a constant temperature purge stage.

[0027] The polycyclic compound containing a six-membered cycloalkane structure used in the present invention can provide a cycloalkane structure and a hydrogenation environment, improve the H / C ratio of the raw material, and make the raw asphalt do not need to be hydrogenated separately; and after the compound containing the six-membered cycloalkane structure is hydrogenated, it will condense to form a compound with an aromatic ring structure, and participate in the stacking of carbon layers and the growth of the mesophase. When it is partially cracked, a certain amount of alicyclic structure and alkyl side chain will be introduced into the system, thereby providing more hydrogen transfer, inhibiting the excessive polymerization of the mesophase asphalt, and facilitating the stacking of molecules and the growth of the mesophase. The preparation method does not need to add a catalyst or remove a hydrogen supply reagent, thus eliminating the energy consumption required for removing the catalyst and the hydrogen supply reagent, and no new impurities are generated during the preparation process. The process is simple and can effectively reduce the preparation cost of the mesophase asphalt.

[0028] In some embodiments of the present invention, the ash content of the asphalt is ≤0.01%, and the quinoline insoluble content is ≤0.01%. In some embodiments of the present invention, the asphalt can be specifically selected from coal tar, petroleum asphalt or biomass asphalt. Impurities such as ash and quinoline insolubles in the asphalt will affect the spinnability of the final product. In the present invention, the ash content of the asphalt used is ≤0.01%, and the quinoline insoluble content is ≤0.01%. The prepared mesophase asphalt has excellent spinnability, and the asphalt used in the present invention does not need to be subjected to additional hydrogenation and other treatments, which simplifies the process steps and is conducive to increasing the production rate.

[0029] In some embodiments of the present invention, the polycyclic compound containing a six-membered cycloalkane structure is at least one of tetralin and decalin, and specifically tetralin, decalin or a mixture of the two can be selected. The present application selects tetralin and / or decalin with a boiling point of 150-400°C and a decomposition temperature below 450°C as hydrogen supply reagents, and its decomposition temperature is relatively matched with the temperature of the mesophase asphalt polymerization reaction. In the stage of mesophase asphalt polymerization, these two substances just decompose, and after decomposition, they can provide hydrogen for the mesophase polymerization reaction. During the polymerization reaction, these two substances condense to form compounds with aromatic ring structures after hydrogen supply, and participate in the stacking of carbon layers and the growth of the mesophase. When they are partially cracked, alicyclic structures and alkyl side chains are introduced into the system, thereby providing more hydrogen transfer, inhibiting excessive polymerization of the mesophase asphalt, facilitating the stacking of molecules and the growth of the mesophase, and can effectively reduce the softening point of the mesophase and improve spinning stability.

[0030] In some embodiments of the present invention, the mass ratio of the asphalt to the polycyclic compound containing a six-membered cycloalkane structure is 5-20:1, and can be specifically selected as 5:1, 10:1, 15:1 or 20:1.

[0031] In some embodiments of the present invention, the polymerization reaction is carried out under stirring conditions, and the stirring rate is 100-1000r / min, and specifically can be selected to be 300r / min. When the stirring rate is too low, it may cause uneven heat transfer and cause some products to overreact. When the stirring rate is too high, some products may not react. The above stirring rate range allows the reactants to fully contact and be evenly distributed, which is beneficial to improving the uniformity of heat transfer and the uniformity of mass transfer during gas purging.

[0032] In the present invention, the polymerization reaction includes a closed temperature increase stage, a constant temperature self-pressure increase stage and a constant temperature purge stage. In some embodiments of the present invention, before the polymerization reaction, the gas in the reaction kettle is replaced with an inert protective gas to obtain a protective atmosphere. The present invention does not specifically limit the type of the inert protective gas, and a commonly used inert protective gas can be used, such as at least one of nitrogen, helium and argon.

[0033] In some embodiments of the present invention, the closed heating stage is heated to the temperature of the polymerization reaction at a heating rate of 1-5°C / min, wherein the temperature of the polymerization reaction is 350-450°C. In some embodiments of the present invention, the closed conditions of the closed heating stage are obtained by closing the air inlet and the air outlet of the reactor. In some embodiments of the present invention, the heating rate can be specifically selected as 1°C / min, 3°C / min or 5°C / min. In the present invention, the above heating rate is conducive to controlling the subsequent reaction degree. In some embodiments of the present invention, the temperature of the polymerization reaction can be specifically selected as 350°C, 390°C, 420°C, 430°C or 450°C. In the present invention, the closed conditions are conducive to the full contact between tetralin and decalin after decomposition and the intermediate phase polymerization, avoiding the decomposition products from directly volatilizing out of the reaction system, and failing to provide hydrogen. If the temperature of the polymerization reaction is too low, the intermediate phase cannot be generated. If the temperature of the polymerization reaction is too high, it is easy to make the intermediate phase grow excessively and lose spinnability. The above heating rate and reaction temperature range are moderate, and the intermediate phase pitch with excellent spinnability can be obtained.

[0034] In some embodiments of the present invention, the constant temperature self-pressurization stage is a constant temperature reaction of 1-12 hours at the temperature of the polymerization reaction. In some embodiments of the present invention, during the constant temperature self-pressurization stage, the reactor is closed, and the asphalt and the polycyclic compound containing the hexacyclic structure undergo cracking and polycondensation, and the cracking will produce gases such as H2, CH4 and C2H6, so the pressure in the reactor will rise. In some embodiments of the present invention, the time of the constant temperature reaction can be specifically selected as 1h, 2h, 4h, 6h, 10h or 12h. If the polymerization reaction time is too short, the reaction is not sufficient, and the hydrogen supply is insufficient. If the polymerization reaction time is too long, the mesophase is over-polymerized, the molecular growth is too large, and its fluidity and spinnability are lost. The above reaction time range is moderate, and an intermediate phase asphalt with excellent spinnability can be obtained.

[0035] In some embodiments of the present invention, the constant temperature purge stage is to pass an inert protective gas into the bottom of the reaction solution at the temperature of the polymerization reaction, and perform constant temperature purge for 1-12 hours, wherein the flow rate of the constant temperature purge is 7-35mL / (g·min). In some embodiments of the present invention, the specific implementation steps of the constant temperature purge stage are as follows: open the air inlet and outlet of the reactor, and pass an inert protective gas into the bottom of the reaction solution at the temperature of the polymerization reaction, and perform constant temperature purge for 1-12 hours. Specifically, the time of the constant temperature purge can be selected as 1h, 4h, 6h, 8h or 12h. Specifically, the flow rate of the constant temperature purge can be selected as 7mL / (g·min), 14mL / (g·min), 28mL / (g·min), or 35mL / (g·min). The above flow unit represents the purge amount of the inert protective gas per unit mass of raw materials per unit time. If the purge flow rate is too large, the viscous components in the system are easily removed, which is not conducive to the melt spinning of the mesophase; if the purge flow rate is too small, it is not conducive to the removal of the isotropic components, affecting the spinnability of the mesophase pitch. The above ratio is moderate, which can ensure the removal of the isotropic components and is conducive to improving the spinnability of the mesophase pitch.

[0036] In some embodiments of the present invention, after the constant temperature purging is completed (i.e., the polymerization reaction is completed), the product obtained by the polymerization reaction is cooled under the protection of an inert protective gas. In some embodiments of the present invention, the cooling method is natural cooling.

[0037] The present invention also provides a spinnable mesophase pitch prepared using any one of the above embodiments.

[0038] The present invention also provides the use of the spinnable mesophase pitch described in the above technical solution in the preparation of carbon fibers.

[0039] The present invention has no special limitation on the method for preparing the carbon fiber in the above-mentioned use, and a conventional preparation method can be used. In some embodiments of the present invention, the method for preparing the carbon fiber comprises the following steps:

[0040] The spinnable mesophase pitch is melt-spun to obtain the asphalt raw fiber.

[0041] The asphalt raw fibers are pre-oxidized and carbonized to obtain carbon fibers.

[0042] In an embodiment of the present invention, the spinning temperature is 365-385°C, the aperture of the spinneret used is 0.15mm, and the rotation speed of the drum is 1000r / min; the pre-oxidation is to put the asphalt raw fiber into a tubular furnace and heat it from room temperature to 150°C at a heating rate of 5°C / min, and then heat it to 200-350°C at a heating rate of 0.5-1°C / min, and keep it warm for 5-15h to obtain pre-oxidized fiber, wherein during the pre-oxidation process, the air flow in the tubular furnace is maintained, and the air flow rate is 0.2-1L / min. The carbonization treatment is to heat the pre-oxidized fiber to 1000-1500°C at a heating rate of 5-10°C / min under the protection of inert protective gas, and keep it warm for 30-60min, wherein the flow rate of the inert protective gas is 20-100mL / min.

[0043] It can be seen from the embodiments of the present invention that the mesophase pitch prepared by the present invention does not need to add a catalyst, nor does it need to remove a hydrogen supply agent, has a high mesophase content, has excellent melt spinning continuity, and has a single filament diameter of less than 15 microns, a single filament continuous spinning time of up to 90 minutes, and a single filament length of up to 20,000 meters. In addition, the mesophase pitch-based carbon fiber obtained by the preparation method of the present invention has excellent mechanical properties, and its tensile strength can reach 1400MPa and its tensile modulus can reach 200GPa.

[0044] The technical scheme of the present invention will be described clearly and completely below in conjunction with the accompanying drawings and embodiments. The embodiments of the present application are only used as examples, and all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0045] like Figure 1 As shown, it is a flow chart of preparing a spinnable mesophase pitch and spinning it in an embodiment of the present invention. The present invention mixes the pitch with decahydronaphthalene and / or tetrahydronaphthalene, stirs under the protection of an inert protective gas, and performs a polymerization reaction to obtain a spinnable mesophase pitch. The obtained mesophase pitch is melt-spun through a spinneret to obtain a pitch raw fiber, which is then pre-oxidized and carbonized to obtain a mesophase pitch-based carbon fiber.

[0046] Example 1

[0047] (1) 130 g of coal tar pitch (ash content ≤ 0.01% by mass, quinoline insoluble content ≤ 0.01% by mass) and 6.5 g of decalin were mixed and placed in a high temperature and high pressure reactor;

[0048] (2) After the gas in the reactor was replaced with N2, the gas inlet and outlet of the high-temperature and high-pressure reactor were closed, and the temperature was raised to 420°C, a polymerization temperature, at a heating rate of 3°C / min under stirring at 300 r / min;

[0049] (3) maintaining the polymerization temperature in a sealed high-temperature and high-pressure reactor for 3 hours;

[0050] (4) opening the air inlet and outlet of the high-temperature and high-pressure reactor, passing N2 into the bottom of the reaction liquid at the polymerization reaction temperature, and purging at a constant temperature for 4 h to obtain a product, wherein the purge gas flow rate is 14 mL / (g·min), and passing the tail gas into a 10% mass concentration ethanol aqueous solution to absorb the organic components therein;

[0051] (5) After the reaction is completed, stirring and heating are stopped, and the product is placed at room temperature to cool naturally under N2 protection to obtain a spinnable mesophase pitch.

[0052] (6) The spinnable mesophase pitch is melt-spun to obtain pitch raw fibers. The spinneret used has an aperture of 0.15 mm and a drum rotation speed of 1000 r / min.

[0053] (7) The asphalt raw fiber was placed in a tubular furnace and heated from room temperature to 150°C at a heating rate of 5°C / min, and then heated to 340°C at a heating rate of 0.5°C / min, and kept warm for 10 hours to obtain pre-oxidized fiber. During the pre-oxidation process, air flow was maintained at a rate of 0.5 L / min. Under N2 protection, the pre-oxidized fiber was heated to 1300°C at a heating rate of 5°C / min, and kept warm for 30 minutes, with a N2 flow rate of 50 mL / min, to obtain carbon fiber.

[0054] Example 2

[0055] A spinnable mesophase pitch was prepared and melt-spun according to the method of Example 1, except that decalin was replaced by 6.5 g of tetralin.

[0056] Example 3

[0057] A spinnable mesophase pitch was prepared and melt-spun according to the method of Example 2, except that the amount of tetralin used was 13 g.

[0058] Example 4

[0059] A spinnable mesophase pitch was prepared and melt-spun according to the method of Example 3, except that the polymerization temperature was 430°C.

[0060] Example 5

[0061] A spinnable mesophase pitch was prepared and melt-spun according to the method of Example 4, except that the purge gas flow rate was 28 mL / (g·min).

[0062] Example 6

[0063] The spinnable mesophase pitch was prepared and melt-spun according to the method of Example 3, except that the pitch used was petroleum pitch (ash content ≤ 0.01% by mass, quinoline insoluble content ≤ 0.01% by mass).

[0064] Comparative Example 1

[0065] The difference between Comparative Example 1 and Example 1 is that in step (1), decahydronaphthalene is replaced by octahydrophenanthrene in an equal amount, the stirring rate is 300 r / min, and other conditions remain unchanged.

[0066] Comparative Example 2

[0067] The difference between Comparative Example 2 and Example 1 is that in step (1), the amount of decalin used is 0 g, and other conditions remain unchanged.

[0068] Comparative Example 3

[0069] The difference between Comparative Example 3 and Example 1 is that in step (1), the amount of decalin used is 36 g, and other conditions remain unchanged.

[0070] Comparative Example 4

[0071] The difference between Comparative Example 4 and Example 1 is that the polymerization reaction temperature is 320°C.

[0072] Comparative Example 5

[0073] The difference between Comparative Example 5 and Example 1 is that the polymerization temperature is 480°C.

[0074] Comparative Example 6

[0075] The difference between Comparative Example 6 and Example 1 is that in step (4), the gas purge flow rate is 3.5 mL / (g·min).

[0076] Comparative Example 7

[0077] The difference between Comparative Example 7 and Example 1 is that in step (4), the gas purge flow rate is 75 mL / (g·min).

[0078] The mesophase content and spinnability of the spinnable mesophase pitch obtained in Examples 1-6 and Comparative Examples 1-7 were tested, and the continuity of the asphalt precursor prepared from the spinnable asphalt, as well as the tensile strength and tensile modulus of the carbon fiber prepared from the asphalt precursor were evaluated. The test results are shown in Table 1:

[0079] Table 1 Test results of Examples 1-6 and Comparative Examples 1-7

[0080]

[0081]

[0082] It can be seen from Table 1 that the mesophase content of the spinnable mesophase pitch obtained by the preparation method of the present application is above 90%, the spinning continuity is good, and the continuous spinning time can reach 90 minutes. The carbon fiber prepared by the spinnable mesophase pitch obtained by the method of the present application has a tensile strength of 1265-1400MPa and a tensile modulus of 189-200GPa, and has relatively excellent mechanical properties. Compared with the present application, the use of octahydrophenanthrene in Comparative Example 1 has no promoting effect on the formation of the mesophase, and cannot effectively reduce the spinning temperature of the mesophase asphalt, nor can it increase the time of continuous and stable spinning; the amount of decahydronaphthalene used in Comparative Examples 2 and 3 is not within the scope of the present application, and the spinning continuity and the mechanical properties of the finally prepared carbon fiber are poor; the polymerization reaction temperatures of Comparative Examples 4 and 5 are not within the polymerization reaction temperature range set in the present application, the mesophase content and the softening point temperature of Comparative Example 4 are low, and the obtained mesophase asphalt cannot be spun, while the mesophase content of Comparative Example 5 is similar to that of the embodiment, but the softening point temperature of Comparative Example 5 is very high, and the asphalt raw fiber prepared in Comparative Example 5 cannot be spun; the gas purge flow rates in Comparative Examples 6 and 7 are not within the gas purge flow rate range set in the present application, the mesophase content and the softening point temperature obtained in Comparative Example 6 are low, and the obtained mesophase asphalt cannot be spun, while the softening point of Comparative Example 7 is higher than that of the embodiment, and the mesophase prepared in Comparative Example 7 cannot be spun.

[0083] The polarizing microscope images of the asphalt raw fibers obtained in Examples 1-6 and Comparative Examples 1-7 are as follows: Figure 2 As shown, Figure 2 A to F correspond to the polarizing microscope images of Examples 1 to 6 observed respectively. Figure 2 gm in corresponds to the polarizing microscope images of Comparative Examples 1-7 observed. Figure 2 The structure is calculated by the dot counting method to calculate the area ratio of the intermediate phase to obtain the intermediate phase content. It can be seen that the spinnable intermediate phase asphalt obtained in the embodiment of the present invention has a high intermediate phase content and a better flow domain structure, which means that the molecules of the intermediate phase asphalt prepared by the present invention have better orientation.

[0084] The molecular weight distribution of the embodiments and comparative examples is as follows Figure 3 As shown, Figure 3 af in the figure correspond to the observed time-of-flight mass spectra of Examples 1-6, respectively. Figure 3 gm in corresponds to the observed time-of-flight mass spectra of Comparative Examples 1-7. Figure 3It can be seen that the purge temperature in Example 4 was increased from 420°C to 430°C, which increased the macromolecular content in the mesophase asphalt to a certain extent. In Example 5, the gas purge flow rate was increased from 14mL / (g·min) to 28mL / (g·min), which significantly reduced the small molecule content in the mesophase asphalt and significantly increased the macromolecular content. Therefore, by adjusting the purge temperature and purge gas velocity, the molecular weight distribution can be regulated to make the mesophase asphalt have better spinnability.

[0085] Embodiment and comparative example The raw silk is pre-oxidized and carbonized to obtain the carbon fiber with the following morphology and structure: Figure 4 As shown, Figure 4 af in the figure correspond to the SEM images of the carbon fiber structures of Examples 1-6 observed respectively. Figure 4 gi in corresponds to the observed SEM images of the carbon fiber structures of Comparative Examples 1-3. Figure 4 As shown in Table 1, the spinnable mesophase pitch obtained in the embodiment of the present invention has good continuous spinning performance, and the diameter of the prepared carbon fiber is less than 15 microns, the surface is smooth and uniform, the cross section is a radial structure, the lamellar structure is obvious, and it has good mechanical properties. The softening point and spinning temperature range of the mesophase pitch prepared in Comparative Examples 1-3 are higher, and the spinnability is not as good as the mesophase pitch prepared in the embodiment.

[0086] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a spinnable mesophase pitch, comprising the following steps: The asphalt is mixed with a polycyclic compound containing a six-membered cycloalkane structure, and a polymerization reaction is carried out under the protection of an inert protective gas to obtain a spinnable mesophase asphalt; the polymerization reaction includes a closed heating stage, a constant temperature self-pressure stage and a constant temperature purge stage.

2. The preparation method according to claim 1, characterized in that: The ash content of the asphalt is ≤0.01% by mass, and the quinoline insoluble matter content is ≤0.01% by mass. The asphalt includes one or more of coal asphalt, petroleum asphalt and biomass asphalt.

3. The preparation method according to claim 1, characterized in that: The polycyclic compound containing a six-membered cycloalkane structure is at least one of tetralin and decalin.

4. The preparation method according to claim 1, characterized in that: The mass ratio of the asphalt to the polycyclic compound containing a six-membered cycloalkane structure is 5-20:

1.

5. The preparation method according to claim 1, characterized in that: The polymerization reaction is carried out under stirring conditions, and the stirring rate is 100-1000r / min.

6. The preparation method according to claim 1, characterized in that: The sealed heating stage is to heat the temperature to the polymerization reaction temperature at a heating rate of 1-5°C / min, wherein the polymerization reaction temperature is 350-450°C.

7. The preparation method according to claim 1 or 6, characterized in that: The constant temperature self-pressure increasing stage is to carry out constant temperature reaction for 1-12 hours at the polymerization reaction temperature.

8. The preparation method according to claim 1 or 6, characterized in that: The constant temperature purging stage is to introduce an inert protective gas into the bottom of the reaction solution at the polymerization reaction temperature for constant temperature purging for 1-12 hours, wherein the flow rate of the constant temperature purging is 7-35 mL / (g·min).

9. A spinnable mesophase pitch prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the spinnable mesophase pitch according to claim 9 in preparing carbon fibers.